Ipsilateral adrenalectomy at the time of radical nephrectomy impacts overall survival. (8th October 2012) - Yap, Stanley A.; Alibhai, Shabbir M.H.; Abouassaly, Robert; Timilshina, Narhari; Margel, David; Finelli, Antonio
Abstract : Study Type – Therapy (case series) Level of Evidence 4 What's known on the subject? and What does the study add? Adrenal‐sparing approaches should be utilized when performing radical nephrectomy unless there are specific concerns for adrenal involvement. Although current literature demonstrates 10‐year cancer control equivalence with adrenal‐sparing approaches, such approaches remain under‐used. Furthermore, we have yet to clearly define the long‐term consequences of an iatrogenic solitary adrenal gland on overall patient health. In our study, we demonstrate worse overall survival in patients undergoing ipsilateral adrenalectomy with radical nephrectomy for renal cell carcinoma. We provide some of the only data demonstrating an association between adrenalectomy and long‐term survival, and further emphasize the importance of adrenal‐sparing approaches when performing radical nephrectomy. OBJECTIVE: To assess the impact of ipsilateral adrenalectomy on overall survival, we performed a population‐level analysis. Ipsilateral adrenal‐gland‐sparing approaches during radical nephrectomy (RN) remain under‐utilized and the long‐term consequences of an iatrogenic solitary adrenal gland are poorly understood. PATIENTS AND METHODS: Using the Ontario Cancer Registry we identified 1651 patients in the province of Ontario, Canada, with pT1a renal cell carcinoma who underwent RN between 1995 and 2004. We linked individual patient information with pathological data from abstracted pathology reports and determined whether the ipsilateral adrenal gland was removed at the time of RN. We utilized univariable and multivariable (adjusting for age, gender, tumour size and tumour grade) Cox proportional hazard models and Kaplan–Meier curves to assess predictors of overall and cancer‐specific survival. RESULTS: The overall rate of ipsilateral adrenalectomy at the time of RN was 30%. Median follow‐up for the cohort was 109 months. Adrenal removal was associated with worse overall survival: 10‐year mortality 26% compared with 20% for those in whom the adrenal gland was left in situ . Factors predictive of worse overall survival on multivariable analysis were increasing age (hazard ratio [HR] 1.07 per year, CI 1.06–1.08), high grade tumours (HR 1.38, 1.00–1.90) and having undergone ipsilateral adrenalectomy (HR 1.23, 1.00–1.50). Ipsilateral adrenalectomy was not predictive of cancer‐specific survival (HR 1.18, 0.78–1.79). CONCLUSIONS: We demonstrated a significant association between ipsilateral adrenalectomy and overall survival. Our findings further support the importance of adrenal‐sparing approaches at the time of RN.